Natural Bioenhancers in Drug Delivery: An Overview - Kumar-Sarangi, Manoj; Chandra-Joshi, Bhuwan; Ritchie, Bob (Puerto Rico Health Sciences Journal, 2018)
When the bioavailability of a drug increases, a corresponding increase in the levels of that drug in the bloodstream occurs. With this, drug efficacy is augmented and the dosage required to yield a specific therapeutic effect diminishes comparably. Until recently, only a few methods have proven effective in enhancing drug bioavailability, among which are the disaggregation of micronized molecules, the use of timedrelease and topical preparations, mechanization, polymorph and crystal form selection, drug solubilisation, and the use of nanotechnology. (Though still at the experimental stage, nanotechnology promises to become a powerful pharmacological tool in the future.) Bioenhancers are agents not possessing any inherent therapeutic effects but that, when combined with active drugs, potentiate the pharmacological effects of those drugs. Hence the current article describes the enhancement of the bioavailability of drug molecules through the utilization of natural bioenhancers.